FLORA OF THE YOZYOVON STATE NATURE MONUMENT AND THE BIOECOLOGICAL CHARACTERISTICS OF POPULUS PRUINOSA SCHRENK - Akbarova Muxayyo Xusanovna; Tohirjonova Hilolaxon (Web of Journals Publishing, 2025)
This article presents the results of research on the composition and bioecological characteristics of plant species in the flora of the Yozyovon State Nature Monument, with a focus on the bioecological properties of Populus pruinosa Schrenk, a species found in this flora.
Keywords: Yozyovon State Nature Monument, Populus pruinosa, riparian ecosystem, Central Fergana deserts.